Utilización de la metodología seis sigma para reducir el tiempo de respuesta vía telefónica, en la resolución de problemas sobre el manejo del sistema informático para clientes de una compañía de desarrollo de software en la ciudad de Guayaquil - Daniel, González Cornejo (2009)
The present work aims to develop, implement and maintain the enterprise base of the project, the principles of a Quality System. To achieve this goal has been to implement the philosophy of Six Sigma DMAIC methodology used strategically by its acronym in English, means: Define, Measure, Analyze, Improve and Control. The main activity of the company is developing software technology for web-focused management. The study is critical of the support given to users on issues related to the use of software. With a view to improvement in this process, the company decided to initiate a Quality System to search for "Reduce response time by phone, in solving problems on the management system for customers." The improvement is observable in a quantitative way in reducing the percentage of calls that exceed the call time of four minutes. It performs an initial assessment of the process, choosing the best solution, implementing the strategy and to verify their effectiveness through controls leading to improvement.